1-3(y-2x)=7+3x-3y

Simple and best practice solution for 1-3(y-2x)=7+3x-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-3(y-2x)=7+3x-3y equation:


Simplifying
1 + -3(y + -2x) = 7 + 3x + -3y

Reorder the terms:
1 + -3(-2x + y) = 7 + 3x + -3y
1 + (-2x * -3 + y * -3) = 7 + 3x + -3y
1 + (6x + -3y) = 7 + 3x + -3y

Add '3y' to each side of the equation.
1 + 6x + -3y + 3y = 7 + 3x + -3y + 3y

Combine like terms: -3y + 3y = 0
1 + 6x + 0 = 7 + 3x + -3y + 3y
1 + 6x = 7 + 3x + -3y + 3y

Combine like terms: -3y + 3y = 0
1 + 6x = 7 + 3x + 0
1 + 6x = 7 + 3x

Solving
1 + 6x = 7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + 6x + -3x = 7 + 3x + -3x

Combine like terms: 6x + -3x = 3x
1 + 3x = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + 3x = 7 + 0
1 + 3x = 7

Add '-1' to each side of the equation.
1 + -1 + 3x = 7 + -1

Combine like terms: 1 + -1 = 0
0 + 3x = 7 + -1
3x = 7 + -1

Combine like terms: 7 + -1 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| 4a+11-a=12 | | .4x=2500000 | | 7z+6=180 | | x^2+xy+y^2=9 | | D+3.03=2 | | 0.0002+0.03=0.92 | | -7r=21 | | 2x(5-2x)=-24 | | -2(c+2.5)-5(1.2c+4)= | | 12x-4y=30(y) | | 82=2+4n | | 108=9r | | 6x-8(a+3)=10 | | -0.5x^2+25x-275=0 | | 175000.00+550.00X=222650 | | 6d^2-13dt-63t^2= | | 45x+20y=80findy | | 0.07(4x+4)=0.28(x+7)-1.68 | | 800=x*1.5 | | 18x+6x=12y^2 | | 3x-5+8x-13=180 | | 21=40x | | 2n^2+4n-3=0 | | 11.5-3y=-48 | | 40x+20y=80 | | 16x^2-2x+5= | | -16x^2+48x+432=0 | | 12+4(x+1)=64 | | 620x=372 | | 5-4(x+7)=-4x-18 | | 9x-6=180 | | 9(x+7)=117 |

Equations solver categories